ANALISIS PERAN SEKOLAH DALAM IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN DARING DI SEKOLAH DASAR KECAMATAN SUMBERMANJING WETAN - Yanti, Yulia Eka; Ali, Imron (Primary Education Journals (Jurnal Ke-SD-An), 2023)
The 2013 curriculum has been used since the 2013/2014 school year in the Indonesian Education System. However, it has become a problem since the outbreak of COVID-19. Elementary schools generally face obstacles in implementing the 2013 curriculum in online learning. This study aimed to determine how the role of schools in implementing the 2013 curriculum in online learning in 3 Elementary Schools in Sumbermanjing Wetan District. This research used desciptive qualitative approach. Researchers used 3 elementary schools (SD) in Sumbermajing Wetan District as samples, namely SDN 1 Sumberagung, MI Nurul Ulum Sumberagung, and Anak Sholeh Full Day Elementary School and used 33 teachers and 45 students in grades 3 to 6. Data collection techniques used were observation, questionnaires, interviews, and documentation. In the process of data analysis, researchers used descriptive statistics with relative frequency distribution tables. The results of this study indicate that, first, in terms of planning, schools play a role in making a number of plans in implementing the 2013 curriculum in online learning during the covid-19 pandemic. Second, in the aspect of learning implementation, the school plays a role in determining teaching and reading materials. Teaching materials are adapted to online learning and can be accessed online. Third, in terms of assessment and evaluation, schools play a role in determining the criteria for assessment and evaluation of online learning using the 2013 curriculum. Finally, schools play a role in overcoming existing obstacles. The implementation of the 2013 curriculum in online learning encountered many obstacles, especially at the beginning of its implementation.